Evaluating the performance of technology transfer offices - Üstündag, Alp; Ugurlu, Seda Yanik; Kilinç, Mehmet Serdar (Emerald, 2011)
PurposeThe purpose of this paper is to investigate the causal relationships among the factors influencing the technology transfer offices' (TTOs) performance.Design/methodology/approachThe fuzzy cognitive maps (FCM) method is used in this study.FindingsThe findings from this research is that TTO human resources, industry research demand, R&D budget of university and economic uncertainty are the most influential factors on the performance of TTOs. The performance outputs which are mostly affected are the factors, licenses, patents, established spin‐offs, industry research contracts and consulting income.Originality/valueThis study provides a contribution by building the mental map among the concepts which are influencing the TTOs' performance. The causal relationships are defined in a non‐hierarchical network model. Indirect effects are considered in examining the TTOs performance. The pair wise influence degrees of the factors are determined by an empirical study. Using the FCM, the impact of factors on the performance of TTOs is investigated.